THE IMPACT OF CREATIVITY AND LEARNING ACTIVITY ON STUDENTS’ UNDERSTANDING OF ABSTRACT MATHEMATICAL MATERIAL - Irfan; Yusuf Rendi Wibowo; Kharisma Romadhon; Frika Fatimah Zahra; Siti Aisyah (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
Understanding abstract mathematics is often a challenge for students, which can affect their overall mastery of the material. This study aims to analyze the influence of students’ creativity and activeness on understanding abstract material in the MI Mathematics course at FITK UIN Raden Fatah Palembang. Using an explanatory quantitative approach, data were collected through a creativity questionnaire and activeness observation. The population consisted of 120 6th-semester students, with a sample of 86 students selected through a purposive sampling technique. The analysis was carried out using a two-way ANOVA test to identify the influence of each variable. The results of the study showed that: (1) creativity has a significant effect on understanding abstract material, (2) activeness also has a significant effect on understanding abstract material, and (3) the interaction between the two has a positive impact on understanding abstract mathematics.